2009
DOI: 10.3945/ajcn.2008.26964
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of iron deficiency in fully breastfed infants at 6 mo of age: comparison of data from 6 studies

Abstract: Among fully breastfed infants with a birth weight >2500 g, IDA is uncommon before 6 mo, but male infants and those with a birth weight of 2500-2999 g are at higher risk of ID and IDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 39 publications
6
69
1
8
Order By: Relevance
“…[11][12][13] Risk factors for IDA in the 6 th month of age, such as maternal anemia, underweight, sex, weight gain, and umbilical cord clamping time are described in the literature. 14,15 As reported by some authors, late-timing of cord clamping, as compared to immediate clamping, might be associated with better hemoglobin values, higher stores of iron at 6 months of age, and lower incidence of anemia. [15][16][17] Unfortunately, time of umbilical cord clamping is not registered during labor by health professionals in Brazil, which makes it impossible to control for such potential bias.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…[11][12][13] Risk factors for IDA in the 6 th month of age, such as maternal anemia, underweight, sex, weight gain, and umbilical cord clamping time are described in the literature. 14,15 As reported by some authors, late-timing of cord clamping, as compared to immediate clamping, might be associated with better hemoglobin values, higher stores of iron at 6 months of age, and lower incidence of anemia. [15][16][17] Unfortunately, time of umbilical cord clamping is not registered during labor by health professionals in Brazil, which makes it impossible to control for such potential bias.…”
Section: Discussionmentioning
confidence: 80%
“…They observed that the occurrence of anemia in exclusively breastfed children at 6 months referenceS of age and birth weight >2500 grams (5.5 pounds) was low in male infants and those with birth weights between 2500-2999 g had higher risks for ID and IDA. 14 The prevalence of ID ranged from 6% in Sweden to 37% in Ghana, while the prevalence of IDA ranged from 2% in Sweden to 16% in Ghana.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the six randomized trials included in the study by Yang et al (4) , only the two Honduran trials compared different durations of EBF. The purpose of Yang et al's observational analysis (i.e.…”
Section: Exclusive Breast-feeding Response To Drs Kalhoff and Dubementioning
confidence: 99%
“…Проведенные исследования выявили удовле-творительную обеспеченность железом детей на грудном вскармливании в возрасте 4 и 5 мес, но значитель-ное снижение эритроцитарных индексов и содержания ферритина, возникающее к 6 и 9 мес жизни. Высокие потребности в железе у детей второго полугодия жизни отчасти обусловлены и его значительными эндогенны-ми потерями -0,022 против 0,014 мг/кг массы тела в сутки у подростков и взрослых [9]. Таким образом, ИГВ до 6-месячного возраста представляет собой фактор риска развития железодефицитного состояния у детей в возрасте 9 мес [10,11].…”
Section: Introductionunclassified